Electron‐Beam‐Induced Perovskite–Brownmillerite–Perovskite Structural Phase Transitions in Epitaxial La2/3Sr1/3MnO3 Films. (19th February 2014) - Yao, Lide; Majumdar, Sayani; Äkäslompolo, Laura; Inkinen, Sampo; Qin, Qi Hang; van Dijken, Sebastiaan
<x xml:space="preserve">Abstract</x> Structural phase transitions driven by oxygen‐vacancy ordering can drastically affect the properties of transition metal oxides. The focused electron beam of a transmission electron microscope (TEM) can be used to control structural phase transitions in epitaxial La2/3Sr1/3MnO3. The ability to induce and characterize oxygen‐deficient structural phases simultaneously in a continuous and controllable manner opens up new pathways for atomic‐scale studies of transition metal oxides and other complex materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>